UJI ANTIFERTILITAS EKSTRAK LIDAH BUAYA (Aloe Vera L.) TERHADAP KUANTITAS SPERMATOZOA DAN EKSPRESI CYCLOOXYGENASE-2 PADA TESTIS MENCIT (Mus musculusL.) - Rica Vera; Dedy Sambahtra (Journal of Indonesian Medical Laboratory and Science, 2022)
The family planning program needs to be carried out as an effort to reduce the rate of population growth. In this case the participation of men is very important and need research about natural ingredients that can be used as antifertility drugs. Aloe vera leaf (Aloe vera L.) is one of the plants that have an antifertility effect so that it can be used as a contraceptive for men. The purpose of this study was to determine the effect of ethanol extract  aloe vera leaves of the quantity of spermatozoa and the expression of Cyclooxygenase-2 (COX-2) in the testes of mice (Mus musculus L.). The research used four treatment groups, namely P0 as a control was given aquadest 0,5 mL, P1 was given extract 15 mg/25g body weight by oral, P2 was given extract 20 mg/25g body weight by oral, and P3 was given extract 25 mg/25g body weight by oral given for 4 weeks. The research used completely randomized sampling method and data were analyzed using One Way ANOVA followed by Bonferroni Post Hoc test 5%. Administration of ethanol extract aloe vera leaves resulted in a decreased sperm quantity and increase expression of COX-2 in the testes of mice so that aloe vera leaves had the opportunity as a herbal contraceptive for men.